The Current Status of the Ketogenic Diet in Psychiatry - Bostock, Emmanuelle C. S.; Kirkby, Kenneth C.; Taylor, Bruce V. M. (Frontiers in Psychiatry, 2017)
Background The ketogenic diet (KD) has been used in treatment-resistant epilepsy since the 1920’s. It has been researched in a variety of neurological conditions in both animal models and human trials. The aim of this review is to clarify the potential role of KD in psychiatry. Methods Narrative review of electronic databases PubMED, PsychINFO and Scopus. Results The search yielded 15 studies that related the use of KD in mental disorders including anxiety, depression, bipolar disorder, schizophrenia, autism spectrum disorder (ASD) and attention deficit hyperactivity disorder (ADHD). These studies comprised nine animal models, four case studies and two open-label studies in humans. In anxiety, exogenous ketone supplementation reduced anxiety-related behaviours in a rat model. In depression, KD significantly reduced depression-like behaviours in rat and mice models in two controlled studies. In bipolar disorder, one case study reported a reduction in symptomatology a second case study no improvement. In schizophrenia, an open-label study in female patients (n=10) reported reduced symptoms after two weeks of KD, a single case study reported no improvement. In a brief report, three weeks of KD in a mouse model normalized pathological behaviours. In ASD an open-label study in children (n=30) reported no significant improvement; one case study a pronounced and sustained response to KD. In ASD, in four controlled animal studies, KD significantly reduced ASD-related behaviours in mice and rats. In ADHD, in one controlled trial of KD in dogs with co-morbid epilepsy, both conditions significantly improved. Conclusions Despite its long history in neurology, the role of KD in mental disorders is unclear. Half of the published studies are based on animal models of mental disorders with limited generalizability to the analogue conditions in humans. The review lists some major limitations including the lack of measuring ketone levels in four studies and the issue of compliance to the rigid diet in humans. Currently there is insufficient evidence for the use of KD in mental disorders and it is not a recommended treatment option. Future research should include long-term, prospective, randomized, placebo-controlled crossover dietary trials to examine the effect of KD in various mental disorders.